Tri Kaya Parisudha–Based Interactive Learning Media for Promoting Global Diversity in Elementary Education - I Komang Adi Wiyanta; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2025)
Global diversity in elementary education is essential to be strengthened in order to develop students’ understanding of intercultural tolerance. This study aims to develop interactive learning media based on the local wisdom of Tri Kaya Parisudha. The development process employed the ADDIE model. Data were collected using a non-test method in the form of questionnaires. Data analysis was conducted using qualitative and quantitative descriptive techniques. Based on the validity assessment, the interactive learning media were evaluated by two subject-matter experts and two learning media experts. The subject-matter experts obtained an average score of 3.8, categorized as very high validity, while the learning media experts obtained an average score of 3.9, also categorized as very high validity. The interactive learning media that had passed the validity stage were then tested for practicality by practitioners or teachers, obtaining an average score of 3.9, categorized as high practicality, while student responses were tested in Class IV A consisting of nine students, with an average score of 3.8, categorized as high practicality. The effectiveness of the media was examined using a one-group pretest–posttest design with 15 student respondents. The correlated t-test results showed a significant value (Sig. 2-tailed) of 0.000, indicating a significance level lower than 0.05 (Sig. < 0.05). Therefore, the interactive learning media based on Tri Kaya Parisudha are considered valid, practical, and effective in improving elementary school students’ understanding of global diversity.